Methods and results of locoregional treatment of brain metastases in patients with non-small cell lung cancer - Patla, Anna; Walasek, Tomasz; Jakubowicz, Jerzy; Blecharz, Paweł; Mituś, Jerzy Władysław; Mucha-Małecka, Anna; Reinfuss, Marian (Contemporary Oncology/Współczesna Onkologia, 2016)
This article presents methods and results of surgery and radiotherapy of brain metastases from non-small cell lung cancer (BMF-NSCLC). Patients with single BMF-NSCLC, with Karnofsky score ≥ 70 and controlled extracranial disease are the best candidates for surgery. Stereotactic radiosurgery (SRS) is recommended in patients with 1–3 BMF-NSCLC below 3–3.5 cm, with minor neurological symptoms, located in parts of the brain not accessible to surgery, with controlled extracranial disease. Whole brain radiotherapy (WBRT) following SRS reduces the risk of local relapse; in selected patients median survival reaches more than 10 months. Whole brain radiotherapy alone is a treatment in patients with multiple metastases, poor performance status, uncontrolled extracranial disease, disqualified from surgery or SRS with median survival 3 to 6 months. There is no doubt that there are patients with BMF-NSCLC who should receive only the best supportive care. There is a debate in the literature on how to select these patients.